Maternal mortality report (London : The Maternal Mortality Committee)
1934-10 1934 1930s 19 pages The Medical Officer for Plymouth says : "Six years ago mothers attending ante-natal clinics had to be persuaded to undergo examination, now they expect it and accept it as the ordinary routine procedure. Thus far has public opinion advanced. The demand for a higher all-round midwifery service will naturally follow." The Medical Officer for Wolverhampton points out that : "The feeling amongst mothers against ante-natal supervision is gradually dying out," but against this one reads the comment of the Medical Officer for Bath, that perhaps the weakest link is the lack of intelligent co-operation on the part of the mother and her friends. The Medical Officer for Leeds, in recording the lowest maternal death rate ever recorded in the city, states his opinion that if more use were made of ante-natal clinics and more attention paid by doctors, mothers and midwives to ante-natal hygiene the rate could be further reduced. The Medical Officer for Hull reports that among the 2,133 mothers attending ante-natal clinics there were only three maternity deaths, and two of these had only had one attendance though advised to attend regularly. The following table given in the Report of the County Medical Officer for Flintshire is of interest : "It is gratifying to be able to indicate in the following Table that not a single death occurred amongst the patients who attended the Authority's Ante-natal Centres during the year under review :— MATERNAL DEATHS — RELATIVE INCIDENCE Number of Deaths per 1,000 Deaths amongst Confinements Maternal deaths Live births Total births Mothers attending Centres 585 0 0 0 Mothers not attending Centres 1,194 10 9.05 8.38 Total confined mothers 1,779 10 5.95 5.62 " The County Medical Officer for Gloucestershire says that it was hoped to be able to open a new centre every three months till a reasonable number was available in all districts. The Committee have been "regretfully" obliged to limit expenditure and no new centre was opened in 1982. (One was opened in March, 1933.) The County Medical Officer for Monmouthshire says that "unfortunately hospital in-patients' waiting lists are so large that many women wait untreated for years and this contributes in no small part to chronic ill health amongst the mothers." The County Medical Officer for Kent says that "prejudice on the women's part is diminishing ... it is noteworthy that second or subsequent attendances are becoming the rule." (12) 292/824/1/20